Analisis Kontribusi Dan Efektivitas Penerimaan Retribusi Pelayanan Pasar Terhadap Pendapatan Asli Daerah Di Kota Kupang - Yohanes Antonio Usfomeny; Petrus E. De Roosari; Cicilia A. Tungga (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to find out how much market service levies contribute to the local income of the city of Kupang, the level of effectiveness as well as the obstacles and efforts in the process of collecting market levies. This research is descriptive qualitative, namely analyzing and describing or illustrating various conditions and situations, various data collected in the form of interview results regarding the problems studied at PD. Kupang City Market. Data collection techniques were carried out using observation, interviews and documentation. The results of the research show that the level of contribution to the receipt of market service levies is classified as very low, the level of effectiveness of the receipt of market service levies is classified as less effective. Obstacles in receiving levies are traders who are in arrears and unpredictable weather. Efforts to increase market levy receipts are by providing outreach, sanctions to traders who are in arrears, selling stalls/kiosks that are still empty and making payments using EDC machines.